Characterization and modification of carbon composite electrodes towards more affordable biosensing applications and integration into fluidic devices - Clark, Kaylee M., author; Henry, Charles S., advisor; Van Orden, Alan, committee member; Prieto, Amy L., committee member; Volckens, John, committee member (Colorado State University. Libraries, 2022)
Fast, accurate, and low-cost medical tests and platforms for biomolecule monitoring are essential to the diagnosis, management, and treatment of many diseases. Electrochemical detection allows for highly sensitive measurements with fast response times. Carbon composite electrodes are an attractive option for electrochemical detection due to their low cost, resistance to biological fouling, large electrochemical solvent windows, and ability to be patterned. However, they often suffer from poor electrocatalytic activity, inability to be molded, and need for complex modifications to effectively detect certain analytes. Combining electrochemistry with fluidics is attractive for a wide array of applications including multiplexing, automation, and high-throughput screening. However, fabrication of electrochemical fluidic devices with integrated carbon electrodes remains a challenge. Thermoplastic electrodes (TPEs) are a new class of composite electrodes discussed in this dissertation that exhibit superior electrochemical properties to typical carbon composite electrodes and can be easily molded into intricate structures. Overall, this dissertation aims to improve carbon composite materials for biosensing applications and integration of electrochemical sensors into fluidic devices. Chapter 2 introduces polycaprolactone (PCL) as a new binder material for TPEs and focuses on the electrochemical characterization of the new material. The PCL-based TPEs have excellent electrochemical activity towards a wide range of analytes as well as high electrical conductivity. Chapter 2 also introduces a simple technique for integrating PCL and carbon composite electrodes into microfluidics. The presented electrode-integrated microfluidic devices are quickly fabricated with a laser cutter using PCL as a bonding layer. As a proof-of-concept application, water-in-oil droplets are electrochemically analyzed. Chapter 3 focuses on use of PCL-based TPEs for enzymatic sensors. The simple fabrication of TPEs also allows catalysts and enzymes to be mixed directly into the material to enhance detection. In Chapter 3, the TPE material is bulk-modified with cobalt phthalocyanine, an electrocatalyst, and glucose oxidase, resulting in a robust glucose sensor that demonstrates long-term current response stability. These sensors can be molded into intricate shapes and sanded for surface renewal (without requiring additional steps to maintain the modification), allowing the sensors to be continuously reused even if damaged or fouled. Chapter 4 investigates the properties of TPEs using two different binders – polycaprolactone (PCL) and polystyrene (PS) – with sanded and heat-pressed surface treatment. XPS and SEM analysis suggested that sanded TPEs have a higher density of graphitic edge planes and improved electrochemistry as a result. Electrochemical detection of O2 and H2O2, which are typically difficult to detect on carbon composites without complex modification, was demonstrated on sanded PS-based TPEs. Additionally, Chapter 4 introduces a new 3D-printed TPE sensor module that is reversibly sealed with magnets. A proof-of-concept sensor for detecting H2O2 in flow with the sensor module is presented. Chapter 5 presents a low-cost flow device, made of inexpensive polyethylene terephthalate (PET) and adhesive films, developed to detect SARS-CoV-2 nucleocapsid (N) protein. Upon addition of a sample in the device, reagents and washes are sequentially delivered to an integrated screen-printed carbon electrode for detection thus automating a full sandwich immunoassay with a single end-user step. The modified electrodes are sensitive and selective for COVID-19 N protein and stable for over seven weeks. The flow device was also successfully applied to detect nine different SARS-CoV-2 variants, including Omicron. In summary, this dissertation presents work to improve carbon composite electrodes, their modification, and integration into fluidic devices for applications as biosensors and beyond. The TPEs presented show improved electrochemical and physical properties, that allow for simple modifications. This work also demonstrates simple electrode integration strategies in several types of fluidic devices for easier and more sensitive detection of biologically relevant analytes. Moreover, the platforms established in this dissertation can be easily adapted for a wide variety of analytes and applications. This work provides materials, methods, and platforms to create more affordable biosensors for medical and other biological sensing.